Nutrition, Exercise and Epigenetics: Ageing Interventions - Yu, Byung Pal (Springer, 2015)
This book focuses on the three most important aspects of ageing research: nutrition, physical exercise and epigenetics. The contributors discuss ways that age-related epigenetic imprints such as DNA methylation and histone acetylation are modified by these two interventions. The emphasis on epigenetics helps to illuminate the underlying mechanisms of anti-ageing interventions, as ageing and disease are predominately epigenetic phenomena.